MENGUAK MAKNA SISTEM INFORMASI AKUNTANSI BAGI PONDOK PESANTREN MODERN AL-RIFAIE 2 DALAM BINGKAI METAFORA AMANAH - Arina Absari, Dyatri Utami (Fakultas Ekonomi, 2024)
Boarding school is a non-formal educational institutions that promote religious knowledge. Boarding school as an educational institution can not be separated from the name of finance. Every finance in boarding school run by the very mandate of course, for every cottage has a system of financial or accounting information systems differ. System Information is a very important thing in an organization, including boarding schools, for this study aims to determine the standpoint of the caregiver, the foundation treasurer, and the treasurer boarding the meaning of accounting information system for schools. This research was conducted in Pondok Pesantren Modern Al-Rifaie 2. The results showed that the accounting information system for schools is a very important thing, a form of trust, the tools students, vital, assessment tool. Is needed and as encouragement to actually responsible for both the first leader to God. Thus obtained intact meaning that the accounting information system is spearheading the implementation of the mandate for the holders of finance at the school.